Work and Mexican American Parent-Adolescent Relationships: The Mediating Role of Parent Well-Being - Wheeler, Lorey A. (2011)
This study of Mexican American two-parent families (N = 246) examined the role of parents’ well-being (i.e., depressive symptoms, role overload) as a potential mechanism through which parent occupational conditions (i.e., self-direction, hazardous conditions, physical activity, work pressure) are linked to parent-adolescent relationship qualities (i.e., warmth, conflict, disclosure). Depressive symptoms mediated the links between maternal and paternal work pressure and parent-adolescent warmth, conflict, and disclosure. For mothers, depressive symptoms also mediated the links between self-direction and mother-adolescent warmth, conflict, and disclosure; for fathers, role overload mediated the links between work pressure and hazardous conditions with father-adolescent warmth.